Mechanisms of Floor Heave in Roadways Adjacent to a Goaf Caused by the Fracturing of a Competent Roof and Controlling Technology - Shuaigang Liu; Jianbiao Bai; Xiangyu Wang; Bowen Wu; Wenda Wu (Shock and Vibration)
In traditional sequential single-wing mining practices, one-entry longwall mining systems make it challenging to efficiently and smoothly transfer mining equipment during a continuous mining sequence. In two-entry longwall systems, the headgate of the current panel and the tailgate of the next panel are excavated parallel to one another, effectively creating space for the transfer of mining equipment. The tailgate of the panel, however, is subjected to high-mining-induced stresses, causing severe floor heave, which seriously affects the efficiency of coal production. In this paper, field measurements and numerical simulation methods are used to reveal the mechanism of floor heave induced by the rupture and instability of a competent roof. The results show that the positional relationship between the adjacent tailgate and the longwall face is divided into three stages. Throughout the three stages, the area in which the coal pillar is not horizontally displaced moves from the center of the pillar to the goaf, and the area of peak vertical stress within the coal pillar shifts from the center of the pillar to the side nearest to the tailgate. Field studies suggest that the proposed technologies can effectively control floor heave in the tailgates of two-entry longwall mining systems.